The Gaze in the Album of Ahmed I - Fetvacı, Emine (Muqarnas, 2015)
This essay explores the visual rhythms of an album prepared for the Ottoman sultan Ahmed I (r. 1603–1617), examines how they direct the gaze, and investigates the tools used to guide the viewer’s experience of the object. The album works as an aid to the “scrutinizing gaze” (imʿān-i naẓar), and the album maker’s interventions were intended to guide viewers to a higher level of understanding by encouraging them to gaze with contemplation. Some of the tactics employed include the inclusion of a vast variety of material with unusual subject matter; the establishment of word-image relationships among the elements on a single page or on an opening of two pages; the loose organization of visual materials to suggest narratives; and the construction of relationships across frames that are at times purely predicated on the visual. Most important, the album pages invite the eye to go back and forth, and to use the comparative gaze.